Design of a PLC Based Temperature Controlled System - AMOSUN, TAIWO; Wasiu Oyediran Adedeji (Universitas Muhammadiyah Sidoarjo, 2023)
Temperature control plays a critical role in various industrial applications, ensuring optimal process efficiency, product quality, and output. The programmable logic controller (PLC) has emerged as a versatile tool for implementing temperature control systems due to its advanced capabilities in computer control, communication, and automation. This work presents an approach for designing a temperature control systems using Programmable logic controller (PLC). The system employs thermostats, which is a form of temperature sensor to detect and convert temperature values into voltage signals, which are then processed by the PLC through ladder algorithms. The temperature status of the thermostats is used to switch OFF or ON electric heaters in a bid to reduce or increase the temperature of a system. The PLC technology enables continuous monitoring and control of temperature, ensuring precise regulation in industrial settings such as material processing, boiler heating, and kiln operations. Additionally, the paper highlights the advantages of PLC-based temperature control systems, including high efficiency, stability, precision, and remote monitoring capabilities. The findings suggest that PLC-based temperature control systems offer promising solutions for achieving reliable and effective temperature management in diverse industrial environments.